2005
DOI: 10.1530/rep.1.00694
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Col1a1, Col1a2 and procollagen I in germ cells of immature and adult mouse testis

Abstract: The objective of this study was to compare the expression of Col1a1, Col1a2, and procollagen I in the seminiferous tubules of immature and adult mice and to characterize the cellular expression pattern of procollagen I in germ cells during spermatogenesis in order to provide necessary groundwork for further functional studies in the process of spermatogenesis. Microarray analysis demonstrated that Col1a1 and Col1a2 were abundantly expressed in the seminiferous tubules of 6-day-old mice compared with 60-day-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 30 publications
6
45
0
2
Order By: Relevance
“…RNA in situ hybridization was also employed to confirm the microarray data showing that Sly transcript was predominantly expressed in spermatids (Toure et al 2005). In our laboratory, we corroborated the microarray data showing col1a1 and col1a2 mRNA expression levels in the seminiferous tubules of immature and adult mice using semi-quantitative RT-PCR (He et al 2005). Adachi and colleagues revealed that 11 genes were upregulated and three genes were downregulated by diethylstilbestrol in 28-day-old mice using cDNA microarray analysis, however, they only confirmed eight out of 11 upregulated genes by real-time RT-PCR (Adachi et al 2002).…”
Section: Reproducibility Is Essential For the Application Of Microarrsupporting
confidence: 74%
“…RNA in situ hybridization was also employed to confirm the microarray data showing that Sly transcript was predominantly expressed in spermatids (Toure et al 2005). In our laboratory, we corroborated the microarray data showing col1a1 and col1a2 mRNA expression levels in the seminiferous tubules of immature and adult mice using semi-quantitative RT-PCR (He et al 2005). Adachi and colleagues revealed that 11 genes were upregulated and three genes were downregulated by diethylstilbestrol in 28-day-old mice using cDNA microarray analysis, however, they only confirmed eight out of 11 upregulated genes by real-time RT-PCR (Adachi et al 2002).…”
Section: Reproducibility Is Essential For the Application Of Microarrsupporting
confidence: 74%
“…Of these, the first three were reported in testis at transcript level (The MGC Project Team 2004, He et al 2005 while the fourth one was reported at protein level (Emkey et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of procollagen I within the seminiferous tubules of immature and adult mice correlates with the process of germ cell attachment and detachment from the basement membrane. The unique distribution pattern of procollagen I in adult mouse testes implies a possible role for COL1A1, COL1A2, and procollagen I in regulating the adhesion of spermatogonia and preleptotene spermatocytes to the basement membrane and the detachment and migration of spermatocytes and spermatids towards the lumen during spermatogenesis (43).…”
Section: Discussionmentioning
confidence: 99%